Loss of miR-200c expression induces an aggressive, invasive, and chemoresistant phenotype in non-small cell lung cancer - Ceppi, Paolo; Mudduluru, Giridhar; Kumarswamy, Regalla; Rapa, Ida; Scagliotti, Giorgio V.; Papotti, Mauro; Allgayer, Heike (Molecular cancer research, 2010)
The development of metastases is the main reason for cancer-related death in non-small cell lung cancer (NSCLC). The initiation of metastasis involves an increase in cell motility mediated by the loss of cell-cell adhesion caused by E-cadherin repression, in a process commonly known as epithelial-to-mesenchymal transition. A role for microRNA-200 family members in regulating epithelial-to-mesenchymal transition has recently been indicated but data about their expression in lung tumors is still unavailable. The present study investigated the expression of miR-200c in a panel of NSCLC cell lines (n = 9), and a strong inverse correlation with invasion was detected. Reintroduction of miR-200c into highly invasive/aggressive NSCLC cells induced a loss of the mesenchymal phenotype by restoring E-cadherin and reducing N-cadherin expression, and inhibited in vitro cell invasion as well as in vivo metastasis formation. Moreover, miR-200c overexpression restored the sensitivity of NCI-H1299 cells to cisplatin and cetuximab. Hypermethylation of the promoter region was found to be responsible for the loss of miR-200c in invasive cells, as evaluated by 5-aza-2'-deoxycytidine treatment, methylation-specific PCR, and bisulfite sequencing. In primary tumor specimens obtained from 69 patients with consecutively resected NSCLC, lower miR-200c expression levels were found to be associated with a poor grade of differentiation (P = 0.04), a higher propensity to lymph node metastases (P < 0.01), and with a lower E-cadherin expression (P = 0.01). These data indicate that the loss of miR-200c expression induces an aggressive, invasive, and chemoresistant phenotype, and that assessment of its expression could contribute to a better clinicopathologic definition of patients with NSCLC.
Gesehen am 30.01.2023